Irenæus. 3die Bogs 40de Kapitel. Tekstudgivelse - Jacobsen, Anders-Christian (Grundtvig-Studier, 1998)
Irenæus. Book III Chapter 40 By Anders-Christian Lund Jacobsen In this article I present and comment on a hitherto unprinted text from Grundtvig’s posthumous writings. The text is a translation of Irenaeus’s Adv. haer. 3,24,1-2. In the Irenaeus text corpus the pericope is part of the conclusion of the argumentation in the third book, the main theme of which is providing arguments for the Father and the Son being one. According to Irenaeus, this can only be maintained if it is simultaneously maintained that the faith which is preserved and transmitted by the Church is the only true one. For the Spirit, which is truth, is only in the Church. Grundtvig probably knows this argumentation, which appears from two verses that he wrote in connection with the translation. In my view Grundtvig translated the text in 1854. In that year he quoted a passage from the text in the preface to the revised translation of the fifth book of Adv. haer., and he recreated the same passage in a verse in Christenhedens Syvstjerne (The Seven Star of Christendom). The reason why Grundtvig translates this pericope from Adv. haer. in 1854 is that he is working on a re-wording of his view of the congregation. He now attributes great importance to the congregation as the place where the Spirit works for faith and salvation. The Spirit is the Spirit of community. This view of the congregation is a natural consequence of the matchless discovery that faith is founded on the confession heard in baptism. This view of the congregation does not, however, reach full maturity until the mid-1850s under the impression of Søren Kierkegaard’s individual Christianity. Irenaeus has been one of the sources of inspiration for this new view of the congregation as a vessel, in which true faith is preserved and handed down, because the Spirit works in the congregation.